A comparative study of fuzzing tools on instrumental analysis - Huang, Xinyan (Nanyang Technological University, 2024)
In the current times, the continuous evolution of technology and integration of technology into our daily lives is unavoidable. People’s reliance on technology has caused the complexity of software programs to increase continuously. Consequently, the detection, mitigation of software vulnerabilities became a more prevalent issue due to technology’s indispensable role in society today. Due to the complexity of software programs these days, it is almost impossible to remove all vulnerabilities hence causing zero-day vulnerability to remain as a prevalent issue in the field of cybersecurity. This emphasises the importance of structured discovery of pre-existing vulnerabilities and patches against it before it can be exploited to reduce security issues to the minimum.